Influence of the diffuse double layer on steady-state voltammetry - Dickinson, E; Compton, R (2011)
The influence of the diffuse double layer on the passage of Faradaic current is investigated for steady-state voltammetry. Both mathematical analysis and numerical solution with the Nernst-Planck-Poisson equations are employed. We report a comprehensive study of the effects of reactant charge, electrode charge, electrode size and quantity of supporting electrolyte. Both infinite and finite electrode kinetics are investigated, as well as distance-dependent electron transfer (tunnelling) and activity effects. Certain combinations of reactant and electrode charge are shown to profoundly alter the predicted current by exclusion of the reactant (Levich effect) or deceleration of apparent kinetics (Frumkin effect), although tunnelling can overcome both effects by moving the plane of electron transfer. The structurally altered double layer at nanoelectrodes is shown to either increase or decrease the predicted current depending on the electrode charge, due to an unscreened electric field. © 2011 Elsevier B.V. All rights reserved.